MEASURING EMPLOYEE JOB SATISFACTION AT HOSPITALS: A LITERATURE REVIEW - Nurhasmadiar Nandini; Agus Aan Adriansyah (STIKes Kepanjen, 2020)
A hospital as a healthcare facility consists of various people with various background, competence, and job description. The method to measure job satisfaction at a hospital might be different from in other organizations. This paper aimed to compare the advantages and disadvantages of the methods and instruments to develop a suggestion for more suitable instrument at hospitals in Indonesia. This was a literature review focusing on the comparison of instruments and measurement of employee satisfaction at hospitals. The results showed that there were several instruments with similar variables used to measure job satisfaction in general institutions and at hospitals. However, several variables need to be added in the instruments to measure job satisfaction of hospital employees related to patients, work safety, and else. Based on the literature review, it can be concluded that several indicators need to be included in every questioner to measure job satisfaction of hospital employees, such as supervisor, salary and workload, relationship with co-workers, and opportunity for promotion.